Assessment of Left Atrial Deformation and Function by 2‐Dimensional Speckle Tracking Echocardiography in Healthy Dogs and Dogs With Myxomatous Mitral Valve Disease. (28th April 2017) - Baron Toaldo, M.; Romito, G.; Guglielmini, C.; Diana, A.; Pelle, N.G.; Contiero, B.; Cipone, M.
Abstract : Background: The assessment of left atrial (LA) function by 2‐dimensional speckle tracking echocardiography (STE) holds important clinical implications in human medicine. Few similar data are available in dogs. Objectives: To assess LA function by STE in dogs with and without myxomatous mitral valve disease (MMVD), analyzing LA areas, systolic function, and strain. Animals: One hundred and fifty dogs were divided according to the American College of Veterinary Internal Medicine classification of heart failure: 23 dogs in class A, 52 in class B1, 36 in class B2, and 39 in class C + D. Methods: Prospective observational study. Conventional morphologic and Doppler variables, LA areas, and STE‐based LA strain analysis were performed in all dogs and results were compared among groups. Correlation analysis was carried out between LA STE variables and other echocardiographic variables. Results: Variability study showed good reproducibility for all the tested variables (coefficient of variation <16%). Left atrial areas, fractional area change, peak atrial longitudinal strain (PALS), peak atrial contraction strain, and contraction strain index (CSI) differed significantly between groups B2 and C + D and all the other groups (overall P < .001), whereas only PALS differed between groups B1 and A ( P = .01). Left atrial areas increased with progression of the disease, whereas LA functional parameters decreased. Only CSI increased nonsignificantly from group A to group B1 and then progressively decreased. Thirty‐one significant correlations ( P < .001, r > .3) were found between conventional left heart echocardiographic variables and LA areas and strain variables. Conclusions and Clinical Importance: Left atrial STE analysis provides useful information on atrial function in the dog, highlighting a progressive decline in atrial function with worsening of MMVD.